2019
DOI: 10.1002/nafm.10326
|View full text |Cite
|
Sign up to set email alerts
|

Using Side‐Scan Sonar and N‐Mixture Modeling to Estimate Atlantic Sturgeon Spawning Migration Abundance

Abstract: Understanding the relationship between number of spawners and recruitment is essential for managing fish populations. Atlantic Sturgeon Acipenser oxyrinchus (ATS) are endangered anadromous fish inhabiting the rivers, estuaries, and marine environments along the Atlantic coast of North America. Atlantic Sturgeon are periodic life history strategists that exhibit both spring and fall spawning migrations. Traditional capture–mark–recapture techniques can be used to estimate spawning run abundance but are resource… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
6
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 13 publications
(6 citation statements)
references
References 39 publications
0
6
0
Order By: Relevance
“…Furthermore, our reader's skill and experience in sonar image interpretation and our use of the same reader over time also likely contributed to the accuracy of the index counts. We are currently working to evaluate this monitoring approach in other Gulf Sturgeon systems; the results presented here add to a growing body of literature demonstrating the successful application of side‐scan sonar to enumerate large‐bodied sturgeons (Flowers and Hightower 2015; Hughes et al 2018; Vine et al 2019; Andrews et al 2020; Bunch 2020).…”
Section: Discussionmentioning
confidence: 98%
See 2 more Smart Citations
“…Furthermore, our reader's skill and experience in sonar image interpretation and our use of the same reader over time also likely contributed to the accuracy of the index counts. We are currently working to evaluate this monitoring approach in other Gulf Sturgeon systems; the results presented here add to a growing body of literature demonstrating the successful application of side‐scan sonar to enumerate large‐bodied sturgeons (Flowers and Hightower 2015; Hughes et al 2018; Vine et al 2019; Andrews et al 2020; Bunch 2020).…”
Section: Discussionmentioning
confidence: 98%
“…Nonetheless, the detection probability associated with the use of side-scan sonar to enumerate large-bodied sturgeons during nonmigratory periods in other large river systems has been estimated by other authors and is both relatively high (i.e., range = 0.78-0.84) and precise (95% CIs range from 0.69 to 0.90; Flowers and Hightower 2015;Hughes et al 2018). Vine et al (2019) estimated a lower detection probability during sturgeon migratory periods, yet counts remained similarly precise across replicates.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Mark and recapture sampling is a standard method to estimate fish population or migrating run size (Hughes et al, 2018). Numerous reports have shown that side‐scan sonar can achieve comparable accuracy to the abundance estimates from the mark and recapture sampling method but takes much less effort (Fleming et al, 2018; Hughes et al, 2018; Vine et al, 2019). For example, Hughes et al (2018) found that side‐scan sonar yielded a narrower 95% confidence interval for white sturgeon abundance estimates with 75% fewer sampling days than the mark and recapture approach.…”
Section: Applications In Fish Monitoringmentioning
confidence: 99%
“…First applied to assess aquatic habitat features in rivers Litts 2008, 2010), its use has expanded to serving as a fisheries survey instrument. Bollinger and Kline (2017) used SSS to successfully derive biomass estimates of fishes utilizing artificial reefs in the Gulf of Mexico, and Fleming et al (2018) and Vine et al (2019) used SSS to estimate the abundance and distribution of adult (i.e., > 1 m total length [TL]) alligator gar Atractosteus spatula and Atlantic sturgeon Acipenser oxyrinchus, respectively. The authors of these studies noted significant increases in the efficiency, versatility, and affordability of SSS when compared to more traditional fisheries sampling methods, indicating a likelihood for continued growth in use of the technology by management agencies.…”
Section: Introductionmentioning
confidence: 99%